Biogenic amines in wine and cheese - Švecová, Blanka; Janovská, Miroslava (University of Pardubice, 2021)
Biogenic amines in ten samples of wine and five samples of cheese were determined using an HPLC-UV-MS method. Inevitable derivatization was performed with the reagent dansyl chloride, and the derivatives prepared were analysed under optimized chromatographic conditions in reversed phase mode. An octadecylsilicagel column (C18) was used for the separation of ten selected biogenic amines derivatives which were eluted using the mobile phase composed of 5 mM ammonium formate and acetonitrile at a flow-rate 0.6 mL min−1 and detected at the wavelength 254 nm. Basic validation of this method was carried out as well. Limits of detection and quantitation, external standard calibration, intra-day repeatability and inter-day reproducibility for spectrophotometric detection were determined. Five various red wines, four white wines and one rosé wine contained very small amounts of biogenic amines. The highest total content was approximately 2.5 mg L−1, which represents a relatively low content in comparison with some results published in literature. Similarly, the content of biogenic amines in cheeses analysed was lower than expected, even in case of fermented cheeses. The highest content was found in one of the typical Czech fermented cheeses called Romadur and being 3.9 mg in 100 g cheese.
Keywords: biogenic amines; dansylation; HPLC; wine; cheese